Peran Anggaran dalam Pengelolaan Risiko Keuangan di Industri Rumah Tangga KWT “Mekar Sari” - Atyka Resty Wulandari; Indah Setiyani; Dhea Putri Fellisa; Tya Rahmawati; Muhammad Aditya Yulianto (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2026)
This study aims to explore the role of budgeting in financial risk management at the KWT “Mekar Sari” Industrial House, which is a home-based business engaged in tofu processing. The focus of the research is on how the budget is applied in dealing with changes in the price of soybean raw materials, managing production costs, and maintaining income stability amid the limitations of small businesses. The methodology applied is a qualitative approach through direct observation, interviews with business actors, and literature review. The findings of this study reveal that although the budgeting process is still simple and based on experience, budgeting plays an important role as a tool in financial planning and control. Determining the amount of raw materials, regulating operational costs, and adjusting product sizes when soybean prices increase are key strategies for maintaining business continuity. The budget also serves KWT “Mekar Sari” in reducing the risk of losses caused by weather changes and business competition. Thus, the budget not only serves as a financial record but also as a strategic tool in improving efficiency, stability, and competitiveness in the home business sector.